The Role of Chemokines in Mediating Graft Versus Host Disease: Opportunities for Novel Therapeutics - Castor, Marina G.; Pinho, Vanessa; Teixeira, Mauro M. (Frontiers in Pharmacology, 2012)
Bone marrow transplantation (BMT) is the current therapy of choice for several malignancies and severe autoimmune diseases. Graft versus host disease (GVHD) is the major complication associated with BMT. T lymphocytes and other leukocytes migrate into target organs during GVHD, become activated and mediate tissue damage. Chemokines are well known inducers of leukocyte trafficking and activation and contribute to the pathogenesis of GVHD. Here, we review the major animal models used to study GVHD and the role of chemokines in mediating tissue damage in these models. The role of these molecules in promoting potential beneficial effects of the graft, especially graft versus leukaemia, is also discussed. Finally, the various pharmacological strategies to block the chemokine system or downstream signalling events in the context of GVHD are discussed.